Boosting K+ Capacitive Storage in Dual‐Doped Carbon Crumples with B–N Moiety via a General Protic‐Salt Synthetic Strategy. (10th December 2021) - Lian, Xueyu; Zhou, Junhua; You, Yizhou; Tian, Zhengnan; Yi, Yuyang; Choi, Jin‐Ho; Rümmeli, Mark H.; Sun, Jingyu
Abstract: The heteroatom co‐doped carbonaceous anodes have readily attracted great attention in potassium‐ion batteries (PIBs), owing to their augmented carbon interlayer distances and increased K + storage sites to induce enhanced capacity value. Nevertheless, the synergistic effect of dual‐doped heteroatoms is still unclear and lacks systematic explorations. In addition, traditional synthetic routes are cumbersome with template removal step, which are normally deficient in product scalability. Herein, a generic protic‐salt strategy is devised to realize sulfur‐, phosphorus‐ or boron‐nitrogen dual‐doped carbon (SNC, PNC, or BNC) via varying the types of protic precursors (e.g., the acid). Throughout comprehensive instrumental probing and theoretical simulation, it is identified that the presence of B–N moiety can harvest high adsorption capability of K + and hence exhibit more obvious pseudo‐capacitance behavior than bare N‐doped carbon counterpart. As a PIB anode, the BNC electrode displays an impressive reversible capacity (360.5 mAh g −1 at 0.1 A g −1 ) and cycle stability (125.4 mAh g −1 at 1 A g −1 after 3000 cycles). In situ/ex situ characterizations further reveal the origin of the excellent electrochemical properties of the BNC electrode. Such a tailorable protic‐salt derived anode material offers new possibilities to advance PIB devices. Abstract : Heteroatom dual‐doped carbons enabled by a general protic‐salt synthetic strategy show promise in K‐ion storage, wherein B/N co‐doped carbon materials affording B–N moiety exhibit obviously enhanced pseudocapacitance behavior to harvest satisfying capacity and outstanding cycle stability.